2019
DOI: 10.1016/j.apnr.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Selecting a theoretical framework to guide a research study of older adults' perceptions and experiences of falling in the hospital

Abstract: Selecting a theoretical framework to guide a research study of older adults' perceptions and experiences of falling in the hospital. Applied Nursing Research, 47, 38-40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…The use of theoretical reference in intervention allows the researcher to understand the investigated health behavior, to direct the planning of actions, to identify effective techniques for health behavior change, and to develop evidence-based practices (15,(24)(25) . When guided by a theory, the researcher has the premises to structure the intervention according to the variables that may influence the studied phenomenon (15) , which, in the case of the HBM, are susceptibility, severity, barriers and perceived benefits, underpinning the methodological decisions (38) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of theoretical reference in intervention allows the researcher to understand the investigated health behavior, to direct the planning of actions, to identify effective techniques for health behavior change, and to develop evidence-based practices (15,(24)(25) . When guided by a theory, the researcher has the premises to structure the intervention according to the variables that may influence the studied phenomenon (15) , which, in the case of the HBM, are susceptibility, severity, barriers and perceived benefits, underpinning the methodological decisions (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Given the magnitude of the problem of falls, there is a recommendation that more interventions be conducted to improve the adherence behavior of the elderly to the PMs (14)(15)(16) and decrease the influence of risk factors, such as beliefs (5,17) . Studies have shown that educational interventions can be effective in modifying health beliefs and behaviors (18)(19)(20)(21) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevant number of productions made by nurses was evidenced, considering the direct care provided by nursing to elderly hospitalized patients, which led to the formation of three categories: clinical assessment made by nurses for fall prevention of hospitalized elderly people (11,(20)(21)24,28,32,38) ; identification of fall risk factors in elderly people (10,(12)(13)(14)17,19,22,27,29,35,(39)(40)(41)(42) ; fall risk prevention strategies for elderly people (11,15-18,23,25-26, 29-31,33-34,36-37) .…”
Section: Qualitative Study N=10mentioning
confidence: 99%
“…In the studies included in this category (10,(12)(13)(14)17,19,22,27,29,35,(39)(40)(41)(42) , the factors identified as fall risk of the hospitalized elderly were related to clinical, cognitive, medication and extrinsic factors. Such studies indicate that failure to identify these factors can produce limited strategies, making their prevention difficult.…”
Section: Identification Of Risk Factors For Falls Among Elderly Peoplementioning
confidence: 99%